Enzymes in farm animal nutrition [ - Bedford, Michael R. [ (Michael Richard)] , 1960-; Partridge, Gary R. (CABI, 2010)
Covering all aspects of the addition of enzymes to animal feeds, this book discusses topics including interactions with animal physiology, economic and environmental impacts and technology. This new edition brings the reader up to date with the considerble advances in feed enzyme technology of the last decade. It includes a discussion of new classes of enzymes introduced into the market place, an exploration of how these products function and the size and scope of their use in the global industry with new methods for evaluation of enzyme responses.